The Prosthetic Influence and Biomechanics on Peri-Implant Strain: a Systematic Literature Review of Finite Element Studies - Julius Maminskas; Algirdas Puisys; Ritva Kuoppala; Aune Raustia; Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research)
Objectives: To systematically review risks of mechanical impact on peri-implant strain and prosthetic influence on stability across finite element studies.